Challenges of Food Packaging Materials - Veronica FILIMON; Mihaela ANDREI (ACROSS)
The present paper is a study on the adaptability of packaging materials to the new pandemic context. Producers of packaging materials for the food industry must ensure the safety and quality of food products. Therefore, there are two problems: if the new biomaterials can ensure food stability, the barrier to pathogens and if the different edible films can provide food coverage. A solution for monitoring changes induced in the packaging could be biosensors. These biosensors can identify changes in pH, which often indicate product alteration. Biosensors could also be used to display various contaminants (bacteria, moulds, viruses). In the process of biomaterials selection, two parameters must be monitored: the food product to be packed with all its properties and the entire food traceability chain. This action should be done in detail. Thus, the system: food product - packaging - the external environment must be analyzed in detail, considering all its valences. All these changes to packaging and the emergence of intelligent bio-packaging must be regarded throughout the food chain. The benefits of these biomaterials used in the food industry would have a beneficial environmental impact. The challenge for packaging manufacturers is to adapt quickly to all the food chain changes, from the factory delivery to the consumer’s table as the final link.